Non-aqueous electrolyte and lithium ion battery
By using nonaqueous electrolyte in lithium-ion batteries, combining lithium hexafluorophosphate, lithium difluorosulfonimide and specific additives, the problems of acidity increase and lithium salt consumption during the battery cycle are solved, and a longer cycle life and lower impedance are achieved.
Patent Information
- Application Number
- CN202510119876.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-01-25
AI Technical Summary
The circulation performance of existing lithium-ion batteries decreases due to acidity increase and lithium salt consumption during the circulation process. How to take into account both impedance reduction and cycle life is a technical problem that needs to be solved urgently.
A nonaqueous electrolyte solution, including nonaqueous organic solvent, lithium hexafluorophosphate, lithium bisfluorosulfonylimide or lithium bis(trifluoromethylsulfonyl)imide, and the compound shown in structural formula 1, is used as the first additive, and by regulating the composition and conductivity of the electrolyte solution, it meets a specific mass percentage content and conductivity range to improve the cycle life of the battery.
It realizes the low acidity state after long-term circulation, effectively improves the cycle life of lithium-ion batteries, reduces the impedance of the battery, and improves its fast charging performance.
Smart Images

Figure CN119581671A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a non-aqueous electrolyte and a lithium ion battery. Background Art
[0002] At present, lithium-ion batteries are widely used in digital devices, electric vehicles, energy storage equipment and other fields due to their advantages of stable cycle and large-scale mass production, and their market share continues to expand. However, with the increase of battery voltage and extreme application scenarios, higher requirements are also put forward for electrolyte parameters such as dielectric constant, conductivity, and liquid range, which requires adjustment of the formula to meet the requirements. Lithium salts and additives are important components of battery electrolytes and directly affect battery performance. At the additive level, a new type of peroxide compound is gradually being used in electrolytes, which has the function of reducing impedance, but the increase in acidity during the cycle leads to a reduction in cycle life. At present, lithium hexafluorophosphate (LiPF6) is widely used commercially due to its low price, good ion conductivity, and good solubility. However, the decomposition rate of LiPF6 will accelerate under acidic conditions. Therefore, in the electrolyte using peroxide compounds as additives, lithium hexafluorophosphate is consumed faster, resulting in a decrease in cycle performance. Therefore, how to balance impedance reduction and cycle life is a technical problem that needs to be solved urgently. Summary of the invention
[0003] In view of the problem that the cycle performance of existing lithium ion batteries decreases due to the increase of acidity and the consumption of lithium salts during the cycle process, the present invention provides a non-aqueous electrolyte and a lithium ion battery.
[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte, comprising a non-aqueous organic solvent, a first lithium salt, a second lithium salt and a first additive, wherein the first lithium salt is lithium hexafluorophosphate, the second lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and the first additive comprises a compound shown in structural formula 1: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 are not are hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The non-aqueous electrolyte meets the following conditions: 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of the first lithium salt in the non-aqueous electrolyte, in %; c is the mass percentage of the second lithium salt in the non-aqueous electrolyte, in %; σ is the conductivity of the non-aqueous electrolyte at 25°C, and its unit is mS / cm.
[0005] Optionally, the non-aqueous electrolyte satisfies the following conditions: 70≤σ*(b+c)≤150, 0.04≤a / c≤0.4.
[0006] Optionally, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) 0.05≤a≤0.8; (2) 5≤b≤15; (3) 2≤c≤8; (4)7≤σ≤12.
[0007] Optionally, the compound represented by structural formula 1 satisfies at least one of the following conditions: (1) R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl; (2) R1 and R2 are each independently selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, or substituted or unsubstituted C6-C20 aryl; (3) R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; (4) R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0008] Optionally, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0009] Optionally, the non-aqueous electrolyte further includes a third lithium salt, and the third lithium salt includes LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10, lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0010] Optionally, the non-aqueous electrolyte further includes a second additive, wherein the second additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a phosphite compound, a borate compound, a nitrile compound or an alkane compound; and / or The cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate and methyl vinyl sulfate; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3: ; In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The phosphite compound includes at least one of trimethyl phosphite, triethyl phosphite, tributyl phosphite, triphenyl phosphite, tri-p-tolyl phosphite, tri-o-tolyl phosphite, tris(trimethylsilane)phosphite and tris(triethylsilane)phosphite; and / or The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
[0011] Optionally, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent and a sulfone solvent.
[0012] Optionally, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0013] In another aspect, the present invention provides a lithium ion battery comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above.
[0014] According to the non-aqueous electrolyte provided by the present invention, the compound shown in structural formula 1 is used as the first additive, and lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide and / or lithium bis(trifluoromethylsulfonyl)imide are used as the first lithium salt and the second lithium salt. The inventors have found that when the mass percentage a of the first additive, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt in the non-aqueous electrolyte and the conductivity σ of the non-aqueous electrolyte at 25°C meet the conditions 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13, the obtained non-aqueous electrolyte can maintain a low acidity state after long-term circulation, and should be The use of lithium-ion batteries can effectively improve the cycle life of lithium-ion batteries. It is speculated that during the battery formation process, some compounds shown in structural formula 1 form a film on the negative electrode surface before non-aqueous organic solvents, which is beneficial to improve the composition of the solid electrolyte interface film on the negative electrode surface, reduce impedance, and improve its fast charging performance; while the unreacted compound shown in structural formula 1 plays a role in repairing the solid electrolyte interface film during the cycle, it is easy to react to generate acid, resulting in the decomposition of lithium hexafluorophosphate. By adding lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(trifluoromethylsulfonyl)imide as the second lithium salt, the second lithium salt can prevent the compound shown in structural formula 1 from reacting with lithium hexafluorophosphate to generate HF and PF5, and FSI is replaced by HF and PF5. -The second lithium salt is coordinated with the compound shown in the structural formula 1 to reduce the acidity of the electrolyte. At the same time, the solvation structure of the second lithium salt affects the interaction between the compound shown in the structural formula 1 and the second lithium salt. The solvation structure of the second lithium salt can reduce the acidity of the electrolyte. + With FSI - The coordination effect promotes FSI - The second lithium salt is coordinated with the compound shown in structural formula 1, and the solvation structure of the second lithium salt is directly related to the conductivity of the non-aqueous electrolyte. Therefore, by further regulating the conductivity of the non-aqueous electrolyte, the first additive, the first lithium salt and the second lithium salt can achieve a synergistic effect, thereby ultimately improving the electrochemical performance of the lithium-ion battery. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] An embodiment of the present invention provides a non-aqueous electrolyte, including a non-aqueous organic solvent, a first lithium salt, a second lithium salt and a first additive, wherein the first lithium salt is lithium hexafluorophosphate, the second lithium salt includes at least one of lithium bis(trifluoromethylsulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and the first additive includes a compound shown in structural formula 1: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 are not are hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The non-aqueous electrolyte meets the following conditions: 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of the first lithium salt in the non-aqueous electrolyte, in %; c is the mass percentage of the second lithium salt in the non-aqueous electrolyte, in %; σ is the conductivity of the non-aqueous electrolyte at 25°C, and its unit is mS / cm.
[0017] The inventors have found that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt and the conductivity σ of the non-aqueous electrolyte at 25°C meet the conditions 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13, the obtained non-aqueous electrolyte can maintain a low acidity state after long-term circulation, and can be effectively applied to lithium-ion batteries to improve the cycle life of lithium-ion batteries. It is speculated that this is because during the battery formation process, some The compound shown in the sub-structure formula 1 forms a film on the negative electrode surface before the non-aqueous organic solvent, which is beneficial to improve the composition of the solid electrolyte interface film on the negative electrode surface, reduce impedance, and improve its fast charging performance; while the unreacted compound shown in the structure formula 1 plays a role in repairing the solid electrolyte interface film during the cycle, it is easy to react to generate acid, resulting in the decomposition of lithium hexafluorophosphate. By adding lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(trifluoromethylsulfonyl)imide as the second lithium salt, the second lithium salt can prevent the compound shown in the structure formula 1 from reacting with lithium hexafluorophosphate to generate HF and PF5, and FSI is replaced by - The second lithium salt is coordinated with the compound shown in the structural formula 1 to reduce the acidity of the electrolyte. At the same time, the solvation structure of the second lithium salt affects the interaction between the compound shown in the structural formula 1 and the second lithium salt. The solvation structure of the second lithium salt can reduce the acidity of the electrolyte. + With FSI - The coordination effect promotes FSI - The second lithium salt is coordinated with the compound shown in structural formula 1, and the solvation structure of the second lithium salt is directly related to the conductivity of the non-aqueous electrolyte. Therefore, by further regulating the conductivity of the non-aqueous electrolyte, the first additive, the first lithium salt and the second lithium salt can achieve a synergistic effect, thereby ultimately improving the electrochemical performance of the lithium-ion battery.
[0018] In a preferred embodiment, the non-aqueous electrolyte satisfies the following conditions: 70≤σ*(b+c)≤150, 0.04≤a / c≤0.4.
[0019] When the mass percentage a of the first additive, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt in the non-aqueous electrolyte and the conductivity σ of the non-aqueous electrolyte at 25°C further meet the above conditions, it is beneficial to further improve the cycle life of the lithium-ion battery and reduce the acidity of the non-aqueous electrolyte after circulation.
[0020] In a specific embodiment, the mass percentage a of the first additive in the non-aqueous electrolyte can be 0.001%, 0.005%, 0.008%, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.18%, 0.2%, 0.22%, 0.28%, 0.3%, 0.32%, 0.38%, 0.4%, 0.42%, 0.48%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of these values.
[0021] In a preferred embodiment, 0.05≤a≤0.8.
[0022] The first additive is used to improve the film-forming quality of the solid electrolyte interface film on the surface of the negative electrode. If the content of the first additive is too low, the impedance reduction effect on the solid electrolyte interface film is limited; if the content of the first additive is too high, the first additive reacts with other components of the non-aqueous electrolyte during the battery charge and discharge cycle, which will cause the acidity of the non-aqueous electrolyte to increase, thereby inducing the decomposition of lithium hexafluorophosphate.
[0023] In a specific embodiment, the mass percentage b of the first lithium salt in the non-aqueous electrolyte can be 2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or a range consisting of any two of these values.
[0024] In a preferred embodiment, 5≤b≤15.
[0025] The first lithium salt is selected from lithium hexafluorophosphate, which serves as the main lithium salt in the non-aqueous electrolyte and provides active lithium ions. If the content of the first lithium salt is too low, it will affect the ion conductivity of the non-aqueous electrolyte, increase the impedance of the lithium-ion battery, and cause the capacity of the lithium-ion battery to decrease; if the content of the first lithium salt is too high, it will cause the viscosity of the non-aqueous electrolyte to increase, which is not conducive to the wetting effect of the non-aqueous electrolyte on the positive and negative electrodes.
[0026] In a specific embodiment, the mass percentage c of the second lithium salt in the non-aqueous electrolyte can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of these values.
[0027] In a preferred embodiment, 2≤c≤8.
[0028] The second lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and is an auxiliary lithium salt in the non-aqueous electrolyte. The fluoride ions in the second lithium salt have strong electron-withdrawing properties, which weakens the coordination effect between anions and cations of the lithium salt, making the ions more active, thereby increasing the conductivity of the electrolyte. More importantly, the coordination of the second lithium salt with the first additive can reduce the effect of the first additive on the acidity of the non-aqueous electrolyte. If the content of the second lithium salt is too low, it is difficult to suppress the increase in the acidity of the non-aqueous electrolyte; if the content of the second lithium salt is too high, it affects the high-temperature cycle performance of the lithium-ion battery.
[0029] In a specific embodiment, the conductivity σ of the non-aqueous electrolyte at 25° C. can be 6 mS / cm, 6.5 mS / cm, 7 mS / cm, 7.5 mS / cm, 7.8 mS / cm, 8 mS / cm, 8.5 mS / cm, 9 mS / cm, 9.5 mS / cm, 10 mS / cm, 10.5 mS / cm, 11 mS / cm, 11.5 mS / cm, 12 mS / cm, or a range consisting of any two of these values.
[0030] In a preferred embodiment, 7≤σ≤12.
[0031] The control of the conductivity σ of the non-aqueous electrolyte is used to regulate the solvation structure of the first lithium salt and the second lithium salt to ensure the coordination between the second lithium salt and the first additive. If the conductivity σ of the non-aqueous electrolyte at 25°C is too low, the non-aqueous electrolyte has poor kinetic performance, the fast charging performance of the lithium-ion battery is poor, and the electrolyte viscosity is high, which will also affect the adsorption and film-forming effect of the first additive on the negative electrode surface. If the conductivity σ of the non-aqueous electrolyte at 25°C is high, the non-aqueous electrolyte has poor thermal stability and the high temperature performance of the lithium-ion battery is deteriorated.
[0032] The conductivity of the non-aqueous electrolyte can be detected using a conductivity meter.
[0033] The conductivity of the non-aqueous electrolyte is mainly affected by ion concentration, solvent polarity, electrolyte viscosity, and additives. The conductivity of the electrolyte can be controlled by adjusting the ratio of lithium salt to non-aqueous organic solvent in the electrolyte, the composition of the non-aqueous organic solvent, the selection of additives, etc.
[0034] In the description of the present invention, the term "C1-C12 alkyl" includes straight-chain alkyl, branched-chain alkyl and cycloalkyl. Similarly, the term "C2-C12 alkenyl" includes straight-chain alkenyl, branched-chain alkenyl and cycloalkenyl. The term "C2-C12 alkynyl" includes straight-chain alkynyl, branched-chain alkynyl and cycloalkynyl. The term "C1-C12 alkylene" includes straight-chain alkylene, branched-chain alkylene and cycloalkylene. The term "C2-C12 alkenylene" includes straight-chain alkenylene, branched-chain alkenylene and cycloalkenylene. The term "C2-C12 alkynylene" includes straight-chain alkynylene, branched-chain alkynylene and cycloalkynylene.
[0035] In the description of the present invention, the term "C1-C12 acyl group" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in a C1-C12 alkyl group are replaced by a carbonyl group. The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C1-C12 acyl group is selected from , where R 14 and R 15 Each is independently selected from a single bond or a C1-C11 alkyl group.
[0036] In the description of the present invention, the term "C2-C12 alkoxy acyl" should be understood in a broad sense. Specifically, it can be understood that a single or multiple carbon atoms in the C2-C12 alkyl group are replaced by The position of the substituted carbon atom is not particularly limited. In a preferred embodiment, the C2-C12 alkoxyacyl group is selected from , where R 16 is selected from a single bond or a C1-C11 alkyl group, R 17 An alkyl group selected from C1-C11.
[0037] In the description of the present invention, the term "C2-C12 ether group" should be understood in a broad sense. Specifically, it can be understood as a C2-C12 alkyl group connecting two adjacent carbon atoms. The number of oxygen atoms in the obtained group may be single or multiple.
[0038] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, and substituted or unsubstituted C6-C20 aryl.
[0039] At this time, the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid. When the compound shown in the structural formula 1 is a hydroperoxide or an organic peracid, it has a higher oxygen content, which can remove reducing impurities in the electrolyte in advance, reduce the amount of gas produced during formation, improve the first coulomb efficiency, and increase the initial discharge capacity of the secondary battery.
[0040] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0041] In some embodiments, in the compound represented by structural formula 1, R1 and R2 are each independently selected from a substituted or unsubstituted C1-C12 alkyl, a substituted or unsubstituted C2-C12 alkenyl, a substituted or unsubstituted C2-C12 alkynyl, or a substituted or unsubstituted C6-C20 aryl.
[0042] At this time, the compound shown in the structural formula 1 is a dialkyl peroxide. When the compound shown in the structural formula 1 is a dialkyl peroxide, it is beneficial to inhibit the co-embedding of solvent molecules and improve the interface compatibility between the electrolyte and the negative electrode.
[0043] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0044] In some embodiments, in the compound represented by structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0045] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from ; R2 is selected from , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0046] At this time, the compound shown in the structural formula 1 is a diacyl peroxide. When the compound shown in the structural formula 1 is a diacyl peroxide, in addition to having the characteristics of improving the battery cycle life, it can also decompose to form inert carbon dioxide to dilute the explosion limit of the combustible gas when the battery is thermally runaway, which is beneficial to improving the battery safety performance.
[0047] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0048] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether.
[0049] At this time, the compound shown in the structural formula 1 is a peroxy acid ester. When the compound shown in the structural formula 1 is a peroxy acid ester, the wettability of the electrolyte to the electrode can be improved, the ohmic internal resistance of the battery can be reduced, and the discharge performance of the battery can be improved.
[0050] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0051] In some embodiments, in the compound represented by the structural formula 1, R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
[0052] At this time, the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate. When the compound shown in the structural formula 1 is a peroxycarbonate or a peroxydicarbonate, it has the effect of promoting the solvation of lithium ions and improving the lithium diffusion performance inside the battery.
[0053] As an example, the compound represented by the structural formula 1 can be selected from the following compounds: .
[0054] In some embodiments, the compound represented by structural formula 1 includes one or more of the following compounds: .
[0055] In some embodiments, the non-aqueous electrolyte further comprises a third lithium salt, wherein the third lithium salt comprises LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
[0056] In some embodiments, the non-aqueous electrolyte further includes a second additive, which includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a phosphite compound, a borate compound, a nitrile compound, a lithium salt additive or an alkane compound.
[0057] In some embodiments, the cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate, and methyl vinyl sulfate.
[0058] In some embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, and methylene disulfonate.
[0059] In some embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, or a compound shown in Structural Formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0060] In some embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate, or a compound shown in formula 3: ; In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3.
[0061] In a preferred embodiment, the phosphate compound shown in the structural formula 3 can be at least one of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0062] In some embodiments, the phosphite compound includes at least one of trimethyl phosphite, triethyl phosphite, tributyl phosphite, triphenyl phosphite, tri-p-tolyl phosphite, tri-o-tolyl phosphite, tri(trimethylsilane)phosphite, and tri(triethylsilane)phosphite.
[0063] In some embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0064] In some embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, and sebacononitrile.
[0065] In some embodiments, the alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
[0066] It should be noted that, unless otherwise specified, in general, the content of any one of the optional substances in the third additive in the non-aqueous electrolyte is less than 10%, preferably, the content is 0.01-5%, and more preferably, the content is 0.1%~2%. Specifically, the content of any one of the optional substances in the third additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of these values.
[0067] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass content of the non-aqueous organic solvent is 65% to 90%.
[0068] Specifically, based on the total mass of the non-aqueous electrolyte as 100%, the mass content of the non-aqueous organic solvent can be 65%, 68%, 71%, 74%, 76%, 78%, 79%, 80%, 81.5%, 82%, 84%, 85%, 86%, 87%, 89%, 90% or a range consisting of any two of these values.
[0069] In some embodiments, the non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.
[0070] In some embodiments, the ether solvent includes a cyclic ether or a chain ether, preferably a chain ether with 3 to 10 carbon atoms and a cyclic ether with 3 to 6 carbon atoms. The cyclic ether may be, but not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF); the chain ether may be, but not limited to, dimethoxymethane, diethoxymethane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether. Since the chain ether has a high solvation ability with lithium ions and can improve ion dissociation, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane, which have low viscosity and can impart high ionic conductivity, are particularly preferred. The ether compound can be used alone or in any combination and ratio. The content of the ether compound is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the high-density lithium-ion battery of the present invention. The volume ratio of the non-aqueous solvent is usually 1% or more, preferably 2% or more, and more preferably 3% or more, and the volume ratio is usually 30% or less, preferably 25% or less, and more preferably 20% or less.
[0071] In some embodiments, the nitrile solvent may specifically be but is not limited to at least one of acetonitrile, glutaronitrile, and malononitrile.
[0072] In some embodiments, the carbonate solvent includes a cyclic carbonate or a chain carbonate, and the cyclic carbonate may be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC); the chain carbonate may be, but is not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC). The content of the cyclic carbonate is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention, but when one is used alone, the lower limit of its content is usually 3% or more by volume, preferably 5% or more by volume, relative to the total amount of solvent in the non-aqueous electrolyte. By setting this range, the decrease in conductivity due to the decrease in the dielectric constant of the non-aqueous electrolyte can be avoided, and it is easy to make the large current discharge characteristics, stability relative to the negative electrode, and cycle characteristics of the non-aqueous electrolyte battery reach a good range. In addition, the upper limit is usually 90% or less by volume, preferably 85% or less by volume, and more preferably 80% or less by volume. By setting this scope, the oxidation / reduction tolerance of nonaqueous electrolyte can be improved, thus contribute to the stability during high temperature storage. The content of linear carbonate is not particularly limited, and relative to the total amount of solvent of nonaqueous electrolyte, it is usually more than 15% by volume, preferably more than 20% by volume, and more preferably more than 25% by volume. In addition, usually the volume ratio is less than 90%, preferably less than 85% by volume, and more preferably less than 80% by volume. By making the content of linear carbonate in the above-mentioned scope, it is easy to make the viscosity of nonaqueous electrolyte reach appropriate range, suppress the reduction of ionic conductivity, and then contribute to make the output characteristics of nonaqueous electrolyte battery reach good scope. When two or more linear carbonates are used in combination, the total amount of linear carbonate is made to meet the above-mentioned scope.
[0073] In certain embodiments, it is also possible to preferably use chain carbonates with fluorine atoms (hereinafter referred to as "fluorinated chain carbonates"). The number of fluorine atoms possessed by the fluorinated chain carbonate is not particularly limited as long as it is more than 1, but is generally less than 6, preferably less than 4. When the fluorinated chain carbonate has a plurality of fluorine atoms, these fluorine atoms can be bonded to the same carbon or to different carbons. As the fluorinated chain carbonate, fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, fluorinated diethyl carbonate derivatives, etc. can be listed.
[0074] The carboxylate solvent includes cyclic carboxylate and / or chain carbonate. Examples of cyclic carboxylate include at least one of γ-butyrolactone, γ-valerolactone, and δ-valerolactone. Examples of chain carbonate include at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), and butyl propionate.
[0075] In some embodiments, the sulfone solvent includes a cyclic sulfone and a chain sulfone. Preferably, in the case of a cyclic sulfone, it is usually a compound with 3 to 6 carbon atoms, preferably 3 to 5 carbon atoms, and in the case of a chain sulfone, it is usually a compound with 2 to 6 carbon atoms, preferably 2 to 5 carbon atoms. The content of the sulfone solvent is not particularly limited, and is arbitrary within the range that does not significantly damage the effect of the lithium ion battery of the present invention. Relative to the total amount of solvent of the non-aqueous electrolyte, the volume ratio is usually 0.3% or more, preferably 0.5% or more, and more preferably 1% or more. In addition, the volume ratio is usually 40% or less, preferably 35% or less, and more preferably 30% or less. In the case of using two or more sulfone solvents in combination, the total amount of the sulfone solvent is sufficient to meet the above range. When the content of the sulfone solvent is within the above range, a non-aqueous electrolyte with excellent high temperature storage stability tends to be obtained.
[0076] It should be emphasized that the non-aqueous electrolyte provided in the present application is not a precursor of a gel electrolyte or a solid electrolyte, nor is it suitable as a precursor of a gel electrolyte or a solid electrolyte. The reason is that the improvement of the electrochemical performance of the secondary battery in the present application requires the compound shown in Structural Formula 1 to participate in the formation of the solid electrolyte interface film (SEI) on the negative electrode surface during the battery charge and discharge formation stage, and the compound shown in Structural Formula 1 remaining in the electrolyte to continuously repair the damaged solid electrolyte interface film (SEI) during the long-term cycle of the battery. As a precursor of a gel electrolyte or a solid electrolyte, there is a polymerization operation to form a gel electrolyte before the battery charge and discharge formation. In the polymerization operation, the organic peroxide shown in Structural Formula 1 reacts with the polymerizable monomer as an initiator, resulting in the consumption of the compound shown in Structural Formula 1, and thus cannot play a corresponding role in the charge and discharge formation and the battery charge and discharge cycle process.
[0077] In some embodiments, the non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
[0078] In some embodiments, the polymerizable monomers include one or more of acrylate monomers (such as methyl acrylate, ethyl acrylate, butyl acrylate), acrylamide monomers (such as acrylamide, N,N'-methylenebisacrylamide), vinyl compound monomers (such as polyvinyl alcohol, vinyl pyrrolidone, vinyl imidazole), epoxy resin monomers (such as bisphenol A epoxy resin), polyethylene oxide monomers, polyacrylonitrile monomers, and siloxane monomers.
[0079] In some embodiments, the non-aqueous electrolyte does not undergo polymerization reaction under light or heating conditions.
[0080] In some embodiments, the non-aqueous electrolyte is in liquid state after formation.
[0081] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and the non-aqueous electrolyte as described above.
[0082] In some embodiments, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel oxide (such as lithium nickel oxide), lithium manganese oxide (such as spinel lithium manganese oxide, layered structure lithium manganese oxide, etc.), lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, and one or more of their doping / coating modified compounds. Preferably, the positive electrode active material includes LiFe 1-x’ M' x’ PO4、LiMn 2-y’ M y’ O4 and LiNi x Co y Mn z M 1-x-y-z At least one of O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0083] In a preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ M' x’ PO4, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1. The lithium-ion battery has a high gram capacity, which can effectively improve the energy density of the battery, and the battery has a charge cut-off voltage of up to 3.8V, a high discharge platform, and shows good cycle stability under the conventional voltage window; and because the iron element is relatively abundant and low in price worldwide, compared with rare and high-priced metals such as cobalt, nickel, and manganese, the use of the above-mentioned positive electrode active material helps to reduce costs and reduce dependence on limited resources.
[0084] In a more preferred embodiment, the positive electrode active material is selected from LiFe 1-x’ Mn x’ PO4, where 0≤x'≤0.5.
[0085] In some specific embodiments, the positive electrode active material may include LiCoO2, LiFePO4, LiFe 0.4Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.
[0086] In some embodiments, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer.
[0087] The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0088] The positive electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0089] In some embodiments, the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel. In a more preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0090] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy.
[0091] In a more preferred embodiment, the negative electrode active material includes at least one of graphite, hard carbon, soft carbon, graphene, and silicon-carbon composite materials.
[0092] In some embodiments, the silicon material is one or more of silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon thin films, 3D porous silicon, and hollow porous silicon.
[0093] In some embodiments, the negative electrode further comprises a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. The negative electrode current collector comprises a metal material that can conduct electrons, preferably, the negative electrode current collector comprises at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the negative electrode current collector is selected from copper foil.
[0094] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0095] The negative electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, a thermoplastic resin such as polyethylene and polypropylene; an acrylic resin; and at least one of styrene butadiene rubber.
[0096] The negative electrode conductive agent includes at least one of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0097] In some embodiments, the secondary battery further includes a separator, and the separator is located between the positive electrode and the negative electrode.
[0098] The diaphragm may be an existing conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0099] The present invention is further described below by way of examples.
[0100] Table 1
[0101] Among them, LiFSI is lithium bis(fluorosulfonyl)imide, LiTFSI is lithium bis(trifluoromethylsulfonyl)imide, DTD is vinyl sulfate, FEC is fluoroethylene carbonate, LiBOB is lithium bis(oxalatoborate), and LiODFB is lithium difluorooxalatoborate.
[0102] Example 1 This embodiment is used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and includes the following steps: (1) Preparation of positive electrode sheet: The positive electrode active material LiFePO4, conductive agent carbon black (SP), conductive agent carbon nanotube (CNT), and polyvinylidene fluoride (PVDF) are mixed in a slurry at a weight ratio of 96:1.5:0.5:2, and then dispersed in N-methylpyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and cut with a mold to obtain positive electrode sheets.
[0103] (2) Preparation of negative electrode sheets: The negative electrode active material graphite, the conductive agent carbon black (SP), the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed in a weight ratio of 95:1:1.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and cut with a mold to obtain negative electrode sheets.
[0104] (3) Preparation of non-aqueous electrolyte: In a glove box filled with argon (water content <10 ppm, oxygen content <10 ppm), fully dried first lithium salt, second lithium salt and additives were quickly added to the solvent. The solvent composition is shown in Table 1. The content of each component in the non-aqueous electrolyte is: 3.0 wt% vinylene carbonate, the selection and content of the first additive, the first lithium salt and the second lithium salt are shown in Table 1. After the non-aqueous electrolyte is prepared, the conductivity is tested at 25°C using a conductivity meter and recorded in Table 1.
[0105] (4) Battery separator: The separator should be 8um polyethylene separator.
[0106] (5) Preparation of lithium-ion battery: The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are laminated to form a lithium-ion battery, vacuum-baked at 75°C for 10 hours, and injected with the above-prepared electrolyte. After standing at 45°C for 48 hours, the battery is placed in an environment of 45°C, a pressure of 3kg is applied, and the battery is charged at 0.05C for 2 hours, 0.1C for 1 hour, and 0.2C for 1 hour, and then stood at 45°C for 2 days (to fully activate the battery) to obtain a lithium-ion battery.
[0107] Embodiments 2 to 28 Examples 2 to 28 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: In the preparation steps of the non-aqueous electrolyte: The solvent composition, the first additive, the selection of the first lithium salt and the second lithium salt in the non-aqueous electrolyte and the added mass fraction are shown in Examples 2 to 28 in Table 1. The solvent composition is adjusted and the conductivity is tested and recorded in Table 1.
[0108] Comparative Examples 1 to 15 Comparative Examples 1 to 15 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that: In the preparation steps of the non-aqueous electrolyte: The solvent composition, the first additive, the selection of the first lithium salt and the second lithium salt in the non-aqueous electrolyte and the added mass fraction are shown in Comparative Examples 1 to 15 in Table 1. The solvent composition is adjusted and the conductivity is tested and recorded in Table 1.
[0109] Performance Testing The lithium-ion battery prepared above was subjected to the following performance tests: 1. Normal temperature cycle performance test: At 25°C, the lithium-ion battery is charged and discharged at a current of 1C, and the capacity retention rate is calculated by the following formula: Capacity retention rate (%) = (discharge capacity of the last cycle / discharge capacity of the first cycle) × 100%, until the capacity retention rate reaches 70%, record the number of cycles.
[0110] 2. After the battery capacity is divided, take the electrolyte and test its acidity by tri-n-propylamine titration to obtain the initial acidity. After 2000 cycles of performance testing at room temperature, disassemble the battery to sample the electrolyte and test its acidity to obtain the acidity after the cycle. Calculate the acidity growth rate by the following formula: Acidity growth rate (%) = (acidity after 2000 cycles - initial acidity) / initial acidity × 100%.
[0111] 3. Normal temperature cycle impedance growth rate test: Test the initial impedance of the battery before normal temperature cycling, and test the battery impedance after 2000 cycles at normal temperature. Normal temperature cycle impedance growth rate (%) = (battery impedance after 2000 cycles / initial impedance before cycle) × 100%.
[0112] Impedance test: At 25°C, use a battery with a SOC of 50% and an electrochemical workstation instrument for testing. Set the frequency range to 1MHz-1mHz and the constant voltage perturbation amplitude to 5mV. Record the experimental data. The first data point with an imaginary part of 0 corresponds to the real part R1, and the second data point with a slope of 0 corresponds to the real part R2. Impedance = R2-R1.
[0113] (1) The test results obtained in Examples 1 to 18 and Comparative Examples 1 to 15 are entered in Table 2.
[0114] Table 2
[0115] It can be seen from the test results of Examples 1 to 18 and Comparative Examples 1 to 15 that when the compound shown in Structural Formula 1 is used as the first additive in the non-aqueous electrolyte, lithium hexafluorophosphate is used as the first lithium salt, at least one of lithium bis(trifluoromethylsulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide is used as the second lithium salt, and the mass percentage a of the first additive, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt in the non-aqueous electrolyte and the conductivity σ of the non-aqueous electrolyte at 25° C. satisfy the conditions 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13, the obtained non-aqueous electrolyte has a lower acidity increase after circulation, which can reduce the degradation of the properties of the non-aqueous electrolyte, improve the cycle life of the lithium ion battery, and reduce the impedance increase. It is speculated that during the battery formation process, some compounds shown in structural formula 1 form a film on the negative electrode surface before non-aqueous organic solvents, which is beneficial to improve the composition of the solid electrolyte interface film on the negative electrode surface, reduce impedance, and improve its fast charging performance; while the unreacted compounds shown in structural formula 1 play a role in repairing the solid electrolyte interface film during the cycle, but they are easy to react to generate acid, resulting in the decomposition of lithium hexafluorophosphate. By adding lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(trifluoromethylsulfonyl)imide as the second lithium salt, the second lithium salt can prevent the compound shown in structural formula 1 from reacting with lithium hexafluorophosphate to generate HF and PF5, and FSI is replaced by HF and PF5. - The second lithium salt is coordinated with the compound shown in the structural formula 1 to reduce the acidity of the electrolyte. At the same time, the solvation structure of the second lithium salt affects the interaction between the compound shown in the structural formula 1 and the second lithium salt. The solvation structure of the second lithium salt can reduce the acidity of the electrolyte. + With FSI- The coordination effect promotes FSI - The second lithium salt is coordinated with the compound shown in structural formula 1, and the solvation structure of the second lithium salt is directly related to the conductivity of the non-aqueous electrolyte. Therefore, by further regulating the conductivity of the non-aqueous electrolyte, the first additive, the first lithium salt and the second lithium salt can achieve a synergistic effect, and finally improve the electrochemical performance of the lithium-ion battery.
[0116] It can be seen from the test results of Examples 1 to 18 that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt and the conductivity σ of the non-aqueous electrolyte at 25°C meet the conditions 70≤σ*(b+c)≤150, 0.04≤a / c≤0.4, and 0.005≤a≤0.8, 5≤b≤15, 2≤c≤8, 7≤σ≤12, it is beneficial to further inhibit the increase in acidity of the non-aqueous electrolyte and extend the cycle life of the lithium-ion battery.
[0117] It can be seen from the test results of comparative examples 1 to 15 that when the mass percentage a of the first additive in the non-aqueous electrolyte, the mass percentage b of the first lithium salt, the mass percentage c of the second lithium salt and the conductivity σ of the non-aqueous electrolyte at 25°C do not meet their range limits, even if the conditions 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8 are met, the lithium-ion battery still does not have good cycle performance and low impedance performance, indicating that the a value, b value, c value and σ value have a strong correlation in improving the electrochemical performance of lithium-ion batteries. Similarly, when the a value, b value, c value and σ value meet their range limits, but the σ*(b+c) value or the a / c value does not meet the above-mentioned preset conditions, it is also impossible to improve the stability of the non-aqueous electrolyte and the cycle performance of the lithium-ion battery.
[0118] (2) The test results obtained in Examples 1 and 19 to 24 are entered in Table 3.
[0119] Table 3
[0120] It can be seen from the test results of Examples 1 and 19 to 24 that in the electrolyte system provided by the present invention, under the conditions of satisfying 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13, the use of different first additives and second lithium salts has a certain effect on improving the cycle life of the lithium ion battery, and can inhibit the increase in the acidity of the non-aqueous electrolyte and the impedance increase of the lithium ion battery, indicating that the electrolyte system provided by the present invention is suitable for different first additives and second lithium salts.
[0121] (3) The test results obtained in Examples 1 and 25 to 28 are entered in Table 4.
[0122] Table 4
[0123] It can be seen from the test results of Examples 1 and 25 to 28 that in the electrolyte system provided by the present invention, further adding other additives (DTD, FEC, LiBOB, LiODFB, etc.) can further improve the cycle life of the lithium-ion battery and reduce the impedance of the lithium-ion battery, indicating that the performance improvement mechanism of other additives for lithium-ion batteries is different from that of the first additive. Further adding other additives is beneficial to improving the performance of lithium-ion batteries from different aspects.
[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: The invention comprises a non-aqueous organic solvent, a first lithium salt, a second lithium salt and a first additive, wherein the first lithium salt is lithium hexafluorophosphate, the second lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide, and the first additive comprises a compound shown in structural formula 1: ; wherein n is 0 or 1; R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C1-C12 acyl, substituted or unsubstituted C2-C12 alkoxyacyl, substituted or unsubstituted C2-C12 ether, and R1 and R2 are not are hydrogen at the same time, R1 and R2 may be connected to each other to form a ring or not; R3 is selected from substituted or unsubstituted C1-C12 alkylene, substituted or unsubstituted C2-C12 alkenylene, substituted or unsubstituted C2-C12 alkynylene, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; when R1, R2, and R3 are substituted, the substituent is alkoxy, hydroxyl, acyl, ester, cyano or halogen; The non-aqueous electrolyte meets the following conditions: 45≤σ*(b+c)≤220, 0.01≤a / c≤0.8, and 0.001≤a≤1, 2≤b≤19, 1≤c≤10, 6≤σ≤13; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of the first lithium salt in the non-aqueous electrolyte, in %; c is the mass percentage of the second lithium salt in the non-aqueous electrolyte, in %; σ is the conductivity of the non-aqueous electrolyte at 25°C, and its unit is mS / cm.
2. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte meets the following conditions: 70≤σ*(b+c)≤150, 0.04≤a / c≤0.
4.
3. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte satisfies at least one of the following conditions: (1)0.05≤a≤0.8; (2)5≤b≤15; (3)2≤c≤8; (4)7≤σ≤12.
4. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula 1 satisfies at least one of the following conditions: (1) R1 is selected from hydrogen, R2 is selected from , substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl, wherein R 10 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl; (2) R1 and R2 are each independently selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, or substituted or unsubstituted C6-C20 aryl; (3) R1 is selected from R2 is selected from substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 11 Selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, substituted or unsubstituted C2-C11 alkynyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C2-C12 ether; (4) R1 is selected from , where R 12 R2 is selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, substituted or unsubstituted C6-C20 aryl or , where R 13 is selected from substituted or unsubstituted C1-C11 alkyl, substituted or unsubstituted C2-C11 alkenyl, and substituted or unsubstituted C2-C11 alkynyl.
5. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula 1 includes one or more of the following compounds: 。 6. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte further includes a third lithium salt, and the third lithium salt includes LiODFP, LiODFB, LiBOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiC(SO2CF3)3, LiClO4, LiAlCl4, LiCF3SO3, LiSO3F, Li2B 10 Cl 10 , lithium chloroborane, lithium trioxalophosphate, a lithium lower aliphatic carboxylate having 4 or less carbon atoms, or at least one of lithium tetraphenylborate.
7. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte further includes a second additive, wherein the second additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a phosphite compound, a borate compound, a nitrile compound or an alkane compound; and / or The cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate and methyl vinyl sulfate; and / or The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, 1,3-propylene sultone and methylene disulfonate; and / or The cyclic carbonate compound includes at least one of vinylene carbonate, vinyl ethylene carbonate, methylene carbonate or the compound shown in structural formula 2: ; In the structural formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or The phosphate compound includes at least one of tris(trimethylsilyl)phosphate, tris(triethylsilyl)phosphate or the compound shown in structural formula 3: ; In the structural formula 3, R 31 , R 32 , R 33 Each is independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, a C6-C12 aryl group, a C6-C12 halogenated aryl group, a -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or The phosphite compound includes at least one of trimethyl phosphite, triethyl phosphite, tributyl phosphite, triphenyl phosphite, tri-p-tolyl phosphite, tri-o-tolyl phosphite, tris(trimethylsilane)phosphite and tris(triethylsilane)phosphite; and / or The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or The nitrile compound comprises at least one of succinonitrile, glutaronitrile, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile; and / or The alkane compound includes at least one of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane and perfluoro(ethylcyclohexane).
8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent and a sulfone solvent.
9. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte does not include a polymerizable monomer and / or a prepolymer obtained by polymerizing a polymerizable monomer.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the non-aqueous electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrochemical cells comprising electrolyte additives, and methods for making and using the same
CN104541388A
Lithium ion electrolyte and lithium ion battery using same
CN109546219A
Electrolyte, preparation method thereof and lithium ion battery
CN110752408A
Non-aqueous electrolyte and lithium ion battery
CN115207462A
Electrolyte and lithium ion battery
CN116154285A
Cited By
Electrolyte composition, lithium ion battery and preparation method thereof
CN122552634A